Examining the Implementation of Gifted and Talented Pilot Program in ADEK’s Public Schools - BUDAIR, SERIN (2018)
Gifted and talented education newly exists within ADEK’s public schools; hence, this study was the first to examine the implementation of the pilot program at three public schools in Cycle 1, Cycle 2 and Cycle 3. The main research questions of the study were to examine the effectiveness of the implementation and the accuracy of outcomes of the program, over several stakeholders, and to check their compliance with NAGC standards. A sequential explanatory mixed methods design was adopted. The methods utilized to collect the data included questionnaire survey, interviews with gifted and talented teachers, social workers, special education teachers, academic vise principal and the head of faculty, in addition to a focus group with grade 4, 5 & 11 gifted and talented students in two schools. Classroom observations and a review of official documents were also conducted. The conclusions were that different deficiencies in the implementation of all program components have arisen from findings, and a room for intensive improvement is a must, especially during the initial level of the program implementation, as a testing phase, before full implementation in all public schools. A set of recommendations are presented to better serve the gifted and talented students of UAE in the future.